Malate metabolism mediated by the cytoplasmic malate dehydrogenase gene MdcyMDH affects sucrose synthesis in apple fruit. Issue 1 (1st November 2022) - Zhang, Lihua; Wang, Changzhi; Jia, Runpu; Yang, Nanxiang; Jin, Ling; Zhu, Lingcheng; Ma, Baiquan; Yao, Yu-xin; Ma, Fengwang; Li, Mingjun
Abstract: The types and proportions of soluble sugar and organic acid in fruit significantly affect flavor quality. However, there are few reports on the crosstalk regulation between metabolism of organic acid and sugar in fruit. Here, we found that the overexpression of cytoplasmic malate dehydrogenase genes ( MdcyMDHs ) not only increased the malate content but also increased the sucrose concentration in transgenic apple calli and mature fruit. Enzyme activity assays indicated that the overexpression of MdcyMDH1 and MdcyMDH5 enhanced sucrose phosphate synthase (SPS) activity in transgenic materials. RNA-seq and expression analysis showed that the expression levels of SPS genes were up-regulated in MdcyMDH1 -overexpressed apple fruit and MdcyMDH5 -overexpressed apple calli. Further study showed that the inhibition of MdSPSB2 or MdSPSC2 expression in MdcyMDH1 transgenic fruit could reduce or eliminate, respectively, the positive effect of MdcyMDH1 on sucrose accumulation. Moreover, some starch cleavage-related genes ( MdBAM6.1/6.2, MdBMY8.1/8.2, MdISA1 ) and the key gluconeogenesis-related phosphoenolpyruvate carboxykinase MdPEPCK1 gene were significantly up-regulated in the transcriptome differentially expressed genes of mature fruit overexpressing MdcyMDH1 . These results indicate that alteration of malate metabolism mediated by MdcyMDH might regulate the expression of MdSPSs and SPS activity via affecting starch metabolism or gluconeogenesis, and thus accelerate sucrose synthesis and accumulation in fruit.